New drugs for multiple sclerosis: new treatment algorithms - Cree, Bruce A C; Hartung, Hans-Peter; Barnett, Michael (Current opinion in neurology, 2022)
PURPOSE OF REVIEW: To discuss recent changes in the multiple sclerosis (MS) treatment algorithm and to present therapies currently in MS clinical trials. RECENT FINDINGS: High efficacy disease modifying therapies are optimally beneficial when used in the early, inflammatory phase of MS. Bruton's tyrosine kinase has emerged as an important therapeutic target for both relapsing and progressive forms of MS. Multiple therapies targeting remyelination failed to provide conclusive evidence of broad therapeutic benefit; however, more targeted approaches offer hope that myelin repair might be achieved resulting in specific clinical improvements. Strategies targeting chronic Epstein-Barr virus infection and dysbiosis of the gut microbiome are the first to link microbial risk factors for MS and therapeutic interventions. SUMMARY: A striking number of diverse treatments under investigation bodes well for development of better and more effective therapies in MS.
Keywords: Multiple Sclerosis; Epstein-Barr Virus Infections; infekce virem Epsteina-Barrové; algoritmy; virus Epsteinův-Barrové; Remyelination; Humans; remyelinizace; Algorithms; Herpesvirus 4, Human; roztroušená skleróza; lidé